Grammatical Errors Analysis in the Recount Text Writing of the Semester 3 Students of English Education Department of IAIN Takengon - Sungkawati Kardi Wahyuningsih (Journal of Educational Analytics, 2022)
The aim of this research study was at finding out the types of grammatical errors in writing recount text of the semester 3 students of English education department of IAIN Takengon. The participants were 50 students of the semester 3 students of English education department of IAIN Takengon in the academic year 2017/2018 that chosen randomly. The study consists of five steps, namely data collection, error identification, error quantification, error description, and error explanation. The research instrument was in the form of a writing assignment. The data were obtained from the students’ writing products. The results of the study are as follow: The total errors found in the students’ writing test are 1179 that divided into fourteen types of error, as they: spelling (14.16%), finite verb (13.15%), preposition (10.96%), error in verb tense (10.52%), pronoun (8.31%), content of usage (7.55%), content of meaning (5.68%), redundancy (5.51%), non-finite verb (5.43%), agreement of singular and plural (4.75%), unintelligibility (4.41%), word choice (3.99%), word order (2.97%), and error in punctuation (2.71%).